IMPROVING NETWORK STABILITY AND LIFE TIME FOR ROUTING IN INTERNET OF HEALTH THINGS BASED ON nRF24L01+ - Rahat Ali Khan, (Spectrum of Engineering Sciences, 2025)
Research advancements in Science and Technology has resulted in the development of various technologies that have huge impact on humans in one way or another. One of the research area focused in research in the application of Internet of Things focusing towards human health care that is Internet of Health Things. Routing in Internet of Health Things require energy power from the battery operated machines to be consumed. This consumption drains the battery of the sensors making the protocol unstable In this paper a new sensor has been proposed to be used in Internet of Health Things to check the performance in terms of energy efficiency of the routing protocol. Previously nRF2401A was used in simulation. The proposed scheme uses is advanced version of nRF2401A.